2020
DOI: 10.1590/s1677-5538.ibju.2020.s106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and surgical assistance in prostate cancer during the COVID-19 Pandemic: implementation of assistance protocols

Abstract: Purpose: Propose an approach of prostate cancer (PCa) patients during COVID-19 pandemic. Material and Methods: We conducted a review of current literature related to surgical and clinical management of patients during COVID-19 crisis paying special attention to oncological ones and especially those suffering from PCa. Based on these publications and current urological guidelines, a manual to manage PCa patients is suggested. Results: Patients suffering from cancer are likely to develop serious complications fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
(71 reference statements)
0
12
0
2
Order By: Relevance
“…Several articles have provided insight into how practitioners should approach this difficult dilemma accordingly to each cancer histology. Suggestions and guidelines are available for head and neck, sino-nasal, spinal, breast, upper tract urothelial, cervical, penile, testicular, pancreatic, kidney, gastric, colorectal, skin, adrenal, liver, prostate, ovarian, endometrial, bladder and endocrine cancer ( Cohen et al, 2020 ; Baumann et al, 2020 ; Werner et al, 2020 ; Tarantola et al, 2013 ; Catanese et al, 2020 ; Vecchione et al, 2020 ; Turri-Zanoni et al, 2020 ; de C. Zequi and Abreu, 2020 ; Gravas et al, 2020 ; O’Leary et al, 2020 ; Casco et al, 2020 ; Katims et al, 2020 ; Berjano et al, 2020 ; Kapuria et al, 2020 ; P. March 25 and 2020, 2021 ; Tachibana et al, 2020 ; Loveday et al, 2020 ; Jones et al, 2020 ; Villani et al, 2020 ; Fligor et al, 2020 ; Sanchez et al, 2020 ; Wallis et al, 2020 ; Topf et al, 2020 ; Matsuo et al, 2020 ; Colombo et al, 2020 ; Campi et al, 2020 ; Raghavan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several articles have provided insight into how practitioners should approach this difficult dilemma accordingly to each cancer histology. Suggestions and guidelines are available for head and neck, sino-nasal, spinal, breast, upper tract urothelial, cervical, penile, testicular, pancreatic, kidney, gastric, colorectal, skin, adrenal, liver, prostate, ovarian, endometrial, bladder and endocrine cancer ( Cohen et al, 2020 ; Baumann et al, 2020 ; Werner et al, 2020 ; Tarantola et al, 2013 ; Catanese et al, 2020 ; Vecchione et al, 2020 ; Turri-Zanoni et al, 2020 ; de C. Zequi and Abreu, 2020 ; Gravas et al, 2020 ; O’Leary et al, 2020 ; Casco et al, 2020 ; Katims et al, 2020 ; Berjano et al, 2020 ; Kapuria et al, 2020 ; P. March 25 and 2020, 2021 ; Tachibana et al, 2020 ; Loveday et al, 2020 ; Jones et al, 2020 ; Villani et al, 2020 ; Fligor et al, 2020 ; Sanchez et al, 2020 ; Wallis et al, 2020 ; Topf et al, 2020 ; Matsuo et al, 2020 ; Colombo et al, 2020 ; Campi et al, 2020 ; Raghavan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that prostate biopsies should be performed in men with suspected high-risk, locally advanced, or symptomatic PCa and this should be done without preceding MRI [19]. The remaining publications related to prostate biopsy are expert consensus recommendations [20][21][22][23][24][25][26][27][28]; most authors recommend that new PSA screening and continuation of diagnostic workup should not be performed until the pandemic is contained and suggest delaying prostate biopsy except in symptomatic patients [21][22][23], PSA > 10ng/mL [31,34,39], suspicion of cT3 disease, PSA doubling time (PSADT) < 6 months [24,27], or in case of medullary compression or obstructive renal failure secondary to PCa suspicion [22,27]. A summary of recommendations for screening and diagnosis is provided in Table 2.…”
Section: Study Characteristics Quality and Level Of Evidencementioning
confidence: 99%
“…Six papers (all of them being either narrative reviews or consensus-based recommendations) addressed the role of active surveillance (AS) in PCa patients and concluded that in very low risk (VLR), low risk (LR), and favorable intermediate risk (FIR) PCa patients, AS is an adequate management strategy [20,24,27,29,30]. For LR and FIR patients, Rodriguez-Sanchez et al and Caicedo-Martinez et al suggest implementation of AS while delaying RP and RT until the pandemic is controlled [27,30], and Kokorovic et al suggest either AS or delaying RP up to 12 months [20]. Detti et al recommend multi-parametric MRI (mpMRI) of the prostate instead of re-biopsy in patients on AS [28].…”
Section: Active Surveillance In Pcamentioning
confidence: 99%
See 1 more Smart Citation
“…Yine lokal invazif, 10 cm'den büyük, vena cavada trombüsü olan ve semptomatik hastalarda tedavinin geciktirilmeden 6 hafta içerinde yapılması gerektiğinin üzerinde durmuştur (6). Literatürde yayınların çoğunda prostat kanserli (PCa) hastalarda cerrahinin pandemi süresince ertelenebileceğini önemle vurgulanmıştır (11)(12)(13). EAU, makroskopik hematürisi ve/veya hematoglobu, görüntüleme yöntemleriyle mesane içerinde kitlesi olan hastalarda sistoskopi ve TUR-MT'nin hemen yapılmasını önerirken ilk TUR-MT patolojisinde kas dokusu izlenmeyen hastaların re-TUR-MT için hazırlanmasını belirtmiştir (14).…”
Section: Bulgularunclassified